Higher Educational Institutions of Russia as a Subject of Economic Activity: Innovations and Their Legal Support - DORSKAIA, Аleksandra А.; PASHENTSEV, Dmitriy А.; KURAKINA, Yuliya V.; DOLAKOVA, Makka I.; SHUTIKOVA, Nataliya S. (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
The article discusses various approaches to the definition of innovation. It is shown that at the present stage, there are economic and legal analysis of innovations and innovative development. The concepts of ‘innovation’, ‘innovation activity’ today are adopted by many international organizations, the European Union institutions, but at the international level, they still do not have a regulatory fix. It is shown that classification of innovations may be different depending on the criteria that form its basis (basic and improving innovation; customized and original innovation; open or closed (i.e. know-how) innovation; industry, intra-sectoral, and inter-state innovations; local or widespread innovation; identified innovations at its own expense, at the expense of the state budget, and at the expense of foreign investors). Authors analyze a possible variety of forms of cooperation between business entities and universities, as well as provide a review on legal support of this type of linkages. It is shown that Russia has a considerable experience in regulating the innovation activity. The first legal document is considered to be manifest on June 17, 1812 ‘On privileges for various inventions and discoveries in the arts and crafts’. The study revealed the rising role of higher education institutions in the innovative development in the Russian Federation.
Keywords: university; innovation; innovative development; legal support; economic activity